Protein Phosphorylation - Prigent, Claude (IntechOpen, 2017)
Protein phosphorylation reactions are carried out in a cell by protein kinases, which predominantly use ATP as a phosphate donor that is transferred and covalently bound to an amino acid on a substrate protein. Protein phosphorylation was discovered in 1954 by Edmond Fischer who shared the Nobel Prize in Medicine or Physiology in 1992 with Edwin Krebs. There are so many kinases that one was called "Just Another Kinase" for JAK kinase. Their counterpart is protein phosphatases that remove phosphates from phosphorylated proteins. Kinases and phosphatases act as switches in the cell that activates or inactivates protein functions. These reactions are reversible; the cell can quickly react to a situation but can then go back to its initial state.